Making the Global Economy Work for All (Revised). (Pamphlet Series; Pamphlet Series, No., 2004)
This paper discusses principles and functions of the IMF. The IMF is a specialized agency of the United Nations system set up by treaty in 1945 to help promote the health of the world economy. Through its work, the IMF helps to keep the world economy running as smoothly as possible. Its work is aimed partly at the prevention of economic and financial crises, but it is also there to help countries out if such a crisis does occur. Member countries provide money (known as quota subscriptions) to the IMF. The IMF can lend from this pool to members in financial difficulty. Quotas, which are based mainly on countries' economic size, determine countries' voting power in the IMF and the limits to what they can borrow. The IMF and World Bank are jointly engaged in an initiative designed to help heavily indebted poor countries (HIPC) cut their debt burdens. Under the HIPC Initiative, debt-reduction is provided to support, policies that promote economic growth and poverty reduction. Policies to reduce poverty need to be supported not only by debt relief, but also by increased aid flows from the 'richer countries and' by improved access for developing countries to industrial countries' export markets.